1966
DOI: 10.1038/bjc.1966.7
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the nervous system in malignant lymphoma in Nigeria.

Abstract: Images Fig. 11 Fig. 12 Fig. 13 Fig. 14 Fig. 1 Fig. 2 Fig. 3 Fig. 4 Fig. 5 Fig. 6 Fig. 7 Fig. 8 Fig. 9 Fig. 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1967
1967
2009
2009

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…The higher incidence found in this study when compared to 10% found in a previous study (12) may reflect the present socio-economic climate in the country with the prohibitive cost of treatment, and therefore progression of the disease with brain involvement. Involvement of the brain is usually associated with widespread organ involvement and has a poor prognosis (11).…”
Section: Discussionmentioning
confidence: 99%
“…The higher incidence found in this study when compared to 10% found in a previous study (12) may reflect the present socio-economic climate in the country with the prohibitive cost of treatment, and therefore progression of the disease with brain involvement. Involvement of the brain is usually associated with widespread organ involvement and has a poor prognosis (11).…”
Section: Discussionmentioning
confidence: 99%
“…Unter den lymphoblastischen Lymphomen im Kindesalter neigen besonders der Burkitt-Typ, das echte Burkitt-Lymphom und das undifferenzierte Lymphom zu einer Meningosis im späteren Verlauf (13,34).…”
unclassified